Optimal threshold of time interval from symptom onset to diagnosis for identification of severity and outcomes in acute symptomatic pulmonary embolism - Wei Xiong; Qiangqiang Qin; Xiaoyang Song; Zhenzhong Deng; Mei Xu; Dongmei Wang; Qihuan Yao; Jianmin Qu; Yong Luo; Fengfeng Han (Annals of Medicine)
Background The more severe the pulmonary embolism (PE), the shorter the time interval from PE symptom onset to diagnosis (OTD). Nevertheless, it is not known how many days of OTD is the optimal threshold for the identification of severe PE or what differences exist in outcomes among PE patients classified by this threshold.Methods Patients with acute symptomatic PE were retrospectively studied to determine the optimal OTD threshold for identifying the severity and outcomes of PE. The differences in one-year mortality, VTE recurrence, major bleeding, and composite outcomes among patients with PE classified by this threshold were compared.Results A total of 1878 patients with PE were finally obtained. All patients were divided into the short OTD (OTD ≤ 1day) group (N = 736) and long OTD (OTD > 1day) group (N = 1142), based on the acquired OTD threshold of one day. The short OTD group had more shock (20.7% vs. 2.9%), hypoxia (62.8% vs. 34.0%), and cardiac arrest (9.2% vs. 1.2%) at PE diagnosis than the long OTD group (all p < 0.001). The occurrence of one-year all-cause mortality (21.7% vs. 16.5%, p = 0.004), PE-related mortality (7.9% vs. 1.9%, p < 0.001), and composite outcomes (28.7% vs. 23.0%, p = 0.006) in the short OTD group were more than that in the long OTD group. In multivariable analyses, OTD > 1day was correlated with a decreased risk of high-risk PE (OR 0.263 [0.117–0.591], p = 0.001) and one-year composite outcomes (HR 0.812 [0.677–0.974], p = 0.025), compared with OTD ≤ 1day.Conclusions PE patients with OTD ≤ 1day had more high-risk PE and worse one-year clinical outcomes, compared to those with OTD > 1day. An OTD of one day could be the optimal threshold for the identification of severity and outcomes of PE.